Reciprocal associations between intuitive eating and positive body image components: A multi-wave, cross-lagged study. (1st November 2022) - Linardon, Jake
Abstract: Intuitive eating is an adaptive style of eating that has gained substantial research attention. However, possible predictors and outcomes of intuitive eating are poorly understood, as prospective study designs addressing this are missing. Since theoretical research indicates that positive body image might enhance – and be enhanced by – intuitive eating, the present study tested for possible reciprocal associations between three components of positive body image (body appreciation, functionality appreciation, and body image flexibility) and intuitive eating. Adult women ( n  = 3039) were invited to complete study measures at baseline (T1), four (T2), and eight month (T3) follow-up. Cross-lagged panel analyses were computed to test for possible reciprocal relationships between intuitive eating and positive body image components. Results showed that intuitive eating and both body appreciation and functionality appreciation were reciprocally related. Higher intuitive eating levels at T1 predicted greater increases in these two positive body image components at T2 (and vice versa). Similarly, higher intuitive eating levels at T2 predicted greater increases in these two positive body image components at T3 (and vice versa). Only unidirectional effects were observed between intuitive eating and body image flexibility: higher intuitive eating levels predicted greater increases in body image flexibility at the subsequent time-point. Findings suggest that intuitive eating and certain components of positive body image might serve to enhance each other over time. Intervention strategies designed to cultivate intuitive eating may also result in concomitant improvements in certain indices of positive body image.